2016
DOI: 10.1111/pce.12652
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast NADPH thioredoxin reductase C, NTRC, controls non‐photochemical quenching of light energy and photosynthetic electron transport in Arabidopsis

Abstract: High irradiances may lead to photooxidative stress in plants, and non-photochemical quenching (NPQ) contributes to protection against excess excitation. One of the NPQ mechanisms, qE, involves thermal dissipation of the light energy captured. Importantly, plants need to tune down qE under light-limiting conditions for efficient utilization of the available quanta. Considering the possible redox control of responses to excess light implying enzymes, such as thioredoxins, we have studied the role of the NADPH th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
120
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 82 publications
17
120
0
Order By: Relevance
“…1, B and C). As reported previously Naranjo et al, 2016aNaranjo et al, , 2016b, the deficiency of NTRC causes more severe impairment on photosynthesis performance than the deficiency of type-f Trxs, as shown by the extensive NPQ at low light intensity, the lower photosynthetic ETR, and the rate of carbon fixation (Fig. 4) in the ntrc mutant.…”
Section: Discussion Ntrc Acts In Concert With Different Types Of Trxsmentioning
confidence: 56%
See 2 more Smart Citations
“…1, B and C). As reported previously Naranjo et al, 2016aNaranjo et al, , 2016b, the deficiency of NTRC causes more severe impairment on photosynthesis performance than the deficiency of type-f Trxs, as shown by the extensive NPQ at low light intensity, the lower photosynthetic ETR, and the rate of carbon fixation (Fig. 4) in the ntrc mutant.…”
Section: Discussion Ntrc Acts In Concert With Different Types Of Trxsmentioning
confidence: 56%
“…2, B and C) of FBPase suggest that the impairment of these redox regulatory systems affects photosynthesis performance. Previous reports have shown that the deficiency of NTRC, but not of Trxs f or Trx x, provokes enhanced nonphotochemical quenching (NPQ) at low light intensity (Naranjo et al, 2016a(Naranjo et al, , 2016b, hence causing a poor efficiency in the utilization of light energy by the ntrc mutant. Thus, as a first step to determine the effect of the combined deficiencies of NTRC and Trxs f or x on photosynthetic performance, we analyzed NPQ in the different lines under study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though ASA and DTT have diverse physiological roles in plant tissues, they have respectively been used as NPQ promoters and NPQ inhibitors to investigate the role of NPQ in plants, as they obviously contribute to changes in NPQ (Bilger and Björkman, 1990; Neubauer, 1993; Mohanty and Yamamoto, 1996; Xu et al, 1999; Ivanov and Edwards, 2000; Yin et al, 2010; Roháček et al, 2014; Naranjo et al, 2015; Quaas et al, 2015). The leaves of the rice plants grown under 600 μmol m −2 s −1 were sprayed with 10 mM DTT in 0.005% (v/v) Tween-80 (DTT treatment), 15 mM ASA in 0.005% (v/v) Tween-80 (ASA treatment), and 0.005% (v/v) Tween-80 in water (control treatment).…”
Section: Methodsmentioning
confidence: 99%
“…Only a few targets were shown to be controlled by NTRC. NTRC functions in the abiotic oxidative stress response (Serrato et al, 2004), starch synthesis (Michalska et al, 2009), Chl synthesis Pérez-Ruiz et al, 2014), the Calvin-Benson cycle (Thormählen et al, 2015), lateral root formation in Arabidopsis (Kirchsteiger et al, 2012), nonphotochemical quenching (Naranjo et al, 2016), as a holdase chaperone function enhancing thermotolerance to Arabidopsis (Chae et al, 2013), and as an electron donor of 2-Cys-peroxiredoxin, thus playing a key role in the detoxification of reactive oxygen species (ROS; Pérez-Ruiz et al, 2006;Spínola et al, 2008;Kirchsteiger et al, 2009). Recent research suggested that cooperative control of chloroplast functions via the ferredoxin-thioredoxin reductase (FTR)/TRX and NTRC pathways is essential for plant viability.…”
mentioning
confidence: 99%